The Influence of Organizational Culture and Work Stress on the Performance of Production Section Employees at PT. Japfa Comfeed Indonesia Tbk Hatchery Parungkuda Unit - Isamartaya; Palahudin; Aldri Yustiansyah (International Journal of Educational and Life Sciences, 2024)
The purpose of this research is to ascertain how employees at PT. Japfa Comfeed Indonesia Tbk Parungkuda Hatchery Unit feel about organisational culture, work stress, and employee performance, as well as how these factors affect employee performance. This study employed a quantitative descriptive and verification methodology. Sixty-one employees served as the research sample for the questionnaire distribution. An ordinal scale is used in the data analysis technique to analyse multiple regression, multiple correlation, coefficient of determination, and hypothesis testing. Employee performance is poor, job stress is adequate, and employee reactions to organisational culture are rather excellent. Employee performance at PT. Japfa Comfeed Indonesia Tbk Parungkuda Hatchery Unit is positively and significantly impacted by both organisational culture and job stress, according to the study's findings. PT. Japfa Comfeed Indonesia Tbk Parungkuda Hatchery Unit, however, work stress has a negative and negligible impact on employee performance, whereas organisational culture has a somewhat favourable and considerable effect.